The terpolymer of neodymium‐catalyzed styrene, isoprene, and butadiene: Efficient synthesis of integral rubber containing atactic styrene–styrene sequences and high Cis‐1, 4 polyconjugated olefins. Issue 8 (24th August 2013) - Xu, Qiang; Li, Li; Guo, Fang; Shi, Zhenghai; Ma, Hongwei; Wang, Yanshai; Wang, Yurong; Li, Yang
<x xml:space="preserve">Abstract</x> The present study focuses on the terpolymer of styrene (St), isoprene (Ip), and butadiene (Bd) synthesized together in cyclohexane at 70°C with neodymium (Nd) compound, alkylaluminum, and chlorinating agent (Cl) rare earth cocatalyst system. The resultants possessed atactic St–St sequences and high cis‐1, 4 polyconjugated olefins in macromolecular chains besides controllable composition. The composition of the St–Ip–Bd terpolymers and molecular weight (Mw), molecular weight distribution (Mw/Mn) were controlled through the adjustment of Nd compound, alkylalumium, monomers feed ratio (St/Ip/Bd), and [Nd]/[monomers]. With the inventory rating of St raised from 15% to 55%, the content of St in the terpolymers got increased from 2% to 15%. And the content of the Ip segments and Bd segments in the terpolymers increased from 33% to 56% and from 28% to 54%, respectively, with the proportion of Ip/Bd varied from 1/2 to 2/1. As the [Nd]/[monomers] varied from 1.0 × 10−3 to 5.0 × 10−4, the molecular weight increased from 1.3 × 104 to 2.7 × 104. According to the proton nuclear magnetic resonance (1H‐NMR) and 13C‐NMR, it was proved that both microstructures of polybutadiene segments and polyisoprene segments were high cis‐1, 4‐configuration. A single glass‐transition temperature was observed in the differential scanning calorimetry curve. POLYM. ENG. SCI., 54:1858–1863, 2014. © 2013 Society of Plastics Engineers